On the Correlation between the Oxygen in Hydrogen Content and the Catalytic Activity of Cathode Catalysts in PEM Water Electrolysis. Issue 11 (22nd November 2021) - Martin, Agate; Trinke, Patrick; Van Pham, Chuyen; Bühler, Melanie; Bierling, Markus; Holzapfel, Peter K. R.; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard
Abstract : Altogether five platinum group metal (PGM) and PGM-free cathode catalysts were investigated in full PEM water electrolysis cells regarding their polarisation behaviour and their hydrogen and oxygen recombination properties. It was shown that the recombination activity of permeated oxygen and evolved hydrogen within the cathodic catalyst layer correlates with the activity of the oxygen reduction reaction (ORR) which was determined ex situ with linear sweep voltammetry. We found that the investigated PGM-free cathode catalysts had a low activity for the ORR resulting in higher measurable oxygen in hydrogen volume fractions compared to the PGM catalysts, which are more active for the ORR. Out of the three investigated PGM-free catalysts, only one commercially available material based on a Ti suboxide showed a similar good polarisation behaviour as the state of the art cathode catalyst platinum, while its recombination activity was the lowest of all catalysts. In addition to the recombination of hydrogen and oxygen on the electrocatalysts, we found that the prevalent carbon-based cathodic porous transport layers (PTL) also offer catalytically active recombination sites. In comparison to an inactive PTL, the measurable oxygen flux using carbon-based PTLs was lower and the recombination was enhanced by microporous coatings with high surface areas.